Acoustic vector sensor - Yeo, Ivan Zhao Rong. (2013)
Our objective is to establish an acoustic vector sensor (AVS) system with a working configuration so data with regards to the beam pattern or other characteristics of the AVS can be determined. This report involves mainly 2 phases. In the first phase, we establish the hardware aspects of the AVS and we propose a design for a pre-amplifier circuit to boost the signal outputs of the AVS. We also show how ground loops and external interference can be detrimental to the signal quality of the AVS and we provided solutions to ensure the resolution of these problems. The optimisation process of the pre-amp circuitry is also explained. In the second phase, we conduct experiments to extract data from the AVS using a professional pre-amplifier and then using the designed pre-amp. Using the results, we show that the steering vector of the AVS is consistent with our expectations.